Effect of maternal age on fetal outcome - Ushadevi Gopalan; Arul Anne Rose S (International Journal of Medical Research and Review, 2015)
Introduction: Low birth weight is one of the most serious challenges in maternal and child health care in both developing and developed countries.Aim of the study: Our aim was to study the correlation between maternal age and fetal outcome measured in terms of fetal weight and perinatal mortality.Materials and Methods: This was a hospital based prospective study conducted in the department of obstetrics and gynecology in our teaching medical college and hospital over a period of 2 years extending from Jan 2011 - Dec 2012. All the cases delivering in this hospital were taken for this study. Total of about 1449 cases were taken for this study.Results: The average age of patients in this study was 23.92 ±4.09. It was observed that there was an increase in birth weight with increasing age up to 40 years. The difference in birth weight between patients less than 20 years of age and in those between 20-29 years of age was found to be statistically significant (p<0.01) while no statistical significance was found in birth weight between the age group 20-29 and 30-39 years (p>0.05). There was an increase in perinatal mortality with increasing age with the least being in those patients less than 20 years of age. The difference in perinatal mortality between the different age groups was found to be statistically insignificant (p>0.05)Conclusion: Increasing maternal age was associated with increase in birth weight. There was no statistically significant association of maternal age with perinatal mortality rate.